Drama and Jokes Reminding Human Rights: Sekber’ 65 Advocacy Human Rights Issues Through Ketoprak - Munanda Okki Saputro; Akhmad Ramdhon; Ahmad Zuber (Yayasan Ilomata, 2026)
The resolution of gross human rights violations during the 1965 Tragedy in Indonesia still faces structural obstacles, particularly through legal mechanisms and state policies. In this situation, the victim community has developed alternative culture-based advocacy strategies. Previous research has indicated that artistic activities serve as an alternative means of advocating for human rights victims, healing trauma, and political struggle. This article analyzes Ketoprak Srawung Bersama (KSB), a performance art practice initiated by the victim community under the Joint SekBer'65 Surakarta, as a cultural strategy in human rights advocacy. Using an interpretive qualitative approach with an ethnographic approach, data was collected through in-depth interviews, participatory observation, and documentation studies. In this analysis, uses Henri Lefebvre's spatial production and Antonio Gramsci's hegemony, as well as Victor Turner's liminality. The results show that KSB functions as a space for the production of alternative narratives, a medium for the negotiation of collective memory, and an affect-based advocacy strategy that challenges the state's hegemonic narrative about the 1965 Tragedy. Performing arts in this context not only represent the experiences of victims but also become a social practice that expands the discourse on human rights in the public sphere, likes agrarian issues, structural inequality, and exploitation. In the performance, the victims of '65 were involved in scriptwriting, acting, and directing. This was a novelty in previous research, which only addressed art as an alternative, but did not show how victims were involved in artistic productions that became a new space for victims of human rights violations.